1992
DOI: 10.1099/00221287-138-11-2363
|View full text |Cite
|
Sign up to set email alerts
|

The catalase-peroxidase of Mycobacterium intracellulare: nucleotide sequence analysis and expression in Escherichia coli

Abstract: The activation of catalase genes in response to oxidative stress may contribute to the intracellular survival of mycobacteria. In this report, the nucleotide sequence of a mycobacterial catalase gene is described. The deduced protein sequence of this Mycobacterium intraceflulare gene (MI83 was 60% identical to the Escherichia coli hydroperoxidase I (HPI) protein, 59% identical to the SdmoneZfu typhimurium (HPI) catalase, and 47% identical to a Bacillus stearothermophilus peroxidase. The MI85 protein, expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Besides their different catalytic behaviour these enzymes also differ in their reduction by dithionite, the narrow pH range for maximal activity, inactivation by hydrogen peroxide and their insensitivity to %amino-1,2,4-triazole. Most of the catalase-peroxidases are tetramers isolated from bacteria (Claiborne and Fridovich, 1979 ;Nadler et al, 1986;Hochman and Goldberg, 1991 ;Yumoto et al, 1990;Morris et al, 1992;Brown-Peterson and Salin, 1993). Those of B L K~~U S stearothermophi1u.s (Loprasert et al, 1988), Comamon c i~ cwizprunsoris (Nies and Schlegel,1 982), Mycobactevium tuIx~rcdosis (Diaz and Wayne, 1974) and Streptomyces cyaneus (Mliki and Zimmermann, 1992) exist as dimers.…”
Section: K E Y W~r D~smentioning
confidence: 99%
“…Besides their different catalytic behaviour these enzymes also differ in their reduction by dithionite, the narrow pH range for maximal activity, inactivation by hydrogen peroxide and their insensitivity to %amino-1,2,4-triazole. Most of the catalase-peroxidases are tetramers isolated from bacteria (Claiborne and Fridovich, 1979 ;Nadler et al, 1986;Hochman and Goldberg, 1991 ;Yumoto et al, 1990;Morris et al, 1992;Brown-Peterson and Salin, 1993). Those of B L K~~U S stearothermophi1u.s (Loprasert et al, 1988), Comamon c i~ cwizprunsoris (Nies and Schlegel,1 982), Mycobactevium tuIx~rcdosis (Diaz and Wayne, 1974) and Streptomyces cyaneus (Mliki and Zimmermann, 1992) exist as dimers.…”
Section: K E Y W~r D~smentioning
confidence: 99%
“…Genes encoding catalase-peroxidase (katG) from slow-growing mycobacteria, such as M. tuberculosis (16) and M. intracellulare (24), have been cloned and sequenced. Polymorphism associated with the katG region has been reported for M. tuberculosis.…”
mentioning
confidence: 99%
“…The gene encoding the M. intracellulare KatG catalase-peroxidase (heat labile, HPI T-catalase) was cloned and expressed in E. coli (Morris et al, 1992). They found that the presence of another catalase activity appeared to be involved in antagonizing isoniazid activity.…”
Section: The Mechanism Of Resistance To Isoniazidmentioning
confidence: 99%
“…The katE gene of M. avium, encoding an HPII-type, heat-stable, M-type catalase-peroxidase has been cloned (Milano et al, 1996) as has the katG gene of M. intracellulare, encoding a HPI-type, heat-labile and T-type catalase (Morris et al, 1992).…”
Section: Mycobacterial Catalase-peroxidasesmentioning
confidence: 99%